Sport specialization, Part I: Does early sports specialization increase negative outcomes and reduce the opportunity for success in young athletes - Myer, G.; Jayanthi, N.; DiFiori, J. P.; Micheli, L. Y. (Sports Health: A Multidisciplinary Approach, 2015)
Context: There is increased growth in sports participation across the globe. Sports specialization patterns, which include year-round training, participation on multiple teams of the same sport, and focused participation in a single sport at a young age, are at high levels. The need for this type of early specialized training in young athletes is currently under debate. Evidence Acquisition: Nonsystematic review. Study Design: Clinical review. Level of Evidence: Level 4. Conclusion: Sports specialization is defined as year-round training (greater than 8 months per year), choosing a single main sport, and/or quitting all other sports to focus on 1 sport. Specialized training in young athletes has risks of injury and burnout, while the degree of specialization is positively correlated with increased serious overuse injury risk. Risk factors for injury in young athletes who specialize in a single sport include year-round single-sport training, participation in more competition, decreased age-appropriate play, and involvement in individual sports that require the early development of technical skills. Adults involved in instruction of youth sports may also put young athletes at risk for injury by encouraging increased intensity in organized practices and competition rather than self-directed unstructured free play.